Rebels : Youth and the Cold War Origins of Identity - Medovoi, Leerom, 1963- (Book collections on Project MUSE., 2005)
Leerom Medovoi argues that youth culture first began to exhibit signs of teen, racial, sexual, gender and generational revolt during the Cold War, which burst into political prominence in the ensuing decades and left a legacy of potent but ambiguous identity politics.